2009
DOI: 10.1007/s10681-009-0097-z
|View full text |Cite
|
Sign up to set email alerts
|

Gynoecious inbred with better combining ability improves yield and earliness in bitter gourd (Momordica charantia L.)

Abstract: This study was the only report for exploiting gynoecy for studying combining ability and hybrid development in bitter gourd. Thirty-six F 1 hybrids and nine inbred lines including one gynoecious line were used to assess combining ability for earliness and yield in bitter gourd Momordica charantia L.). Among parents, gynoecious parent; DBGy-201 showed maximum GCA effect in desirable direction for node to first female flower, days to first picking, numbers of fruits and yield per plant. The parent, P 6 (Priya) e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 13 publications
3
7
0
Order By: Relevance
“…Evaluation of parents with mean performance revealed that the genotype Kasi Harit (14.82) followed by Vadhalagundu local (17.36) were preferred as they would serve as good donors for developing hybrids with desirable sex ratio. Dey et al (2007) reported the similar result of narrow sex ratio in bitter gourd. Observation on days to first harvest is yet another indicator of the earliness in any crop especially vegetables hybrids which could fetch premium price and catch the early market.…”
Section: Resultssupporting
confidence: 55%
“…Evaluation of parents with mean performance revealed that the genotype Kasi Harit (14.82) followed by Vadhalagundu local (17.36) were preferred as they would serve as good donors for developing hybrids with desirable sex ratio. Dey et al (2007) reported the similar result of narrow sex ratio in bitter gourd. Observation on days to first harvest is yet another indicator of the earliness in any crop especially vegetables hybrids which could fetch premium price and catch the early market.…”
Section: Resultssupporting
confidence: 55%
“…However, the utilisation of gynoecy is economical and easier for exploiting hybrid vigour in many cucurbits including bitter gourd (Behera, 2004) that have high male: female sex ratio. Using gynoecious line as one parent in hybrid breeding, it showed positive impact in terms of yield and earliness (Dey et al, 2010;Gangadhara Rao et al, 2018). Keeping in view the above facts, the present investigation was carried out to examine the extent of heterosis in 28 F 1 hybrids by using eight diverse parents.…”
Section: Issn: 2319-7706 Volume 7 Number 11 (2018)mentioning
confidence: 99%
“…Improving fruit yield requires adequate information regarding the nature of GCA and SCA available in a wide array of genetic materials to be used in hybridization programmes. Several authors have used different genetic analyses to study combining ability in cucumber for fruit yield and yield components (Lopez-Sese and Staub, 2002;Xing Fang et al, 2004;Munshi et al, 2006;Mule et al, 2011;Sarkar and Sirohi, 2011;Singh et al, 2011;Olfati et al, 2012;Ene et al, 2018) and gynoecious sex expression (Wahid et al, 2003;Staub et al, 2005;Dey et al, 2010;Singh et al, 2011;Pati et al, 2015). Combining ability studies have been conducted by Adel and Ali (2013) Golabadi et al (2015) and Ene et al (2018), but these authors used elite parental lines to make crosses.…”
Section: Introductionmentioning
confidence: 99%